The Analysis of Antenatal Care During Covid-19 Pandemics in The Working Area of Public Health Center of Tangerang City - Triana Indrayani1, Vivi Silawati1, Retno Widowati2, Sukri Palutturi3, Ridwan Amiruddin4 (Indian Journal of Forensic Medicine & Toxicology, 2020)
Covid-19 spreads from one person to another person through close contact in the form of droplets torespiration track. The physiological changes that happen to the body system is primarily on respiration andimmune system. Such changes give higher possibility on pregnant mothers to be infected by covid-19. Inorder to decrease the infection risk, national policy suggests to omit hospital visit which is not important andchanges it into distance care or virtual visit using phone or video call. Quality Antenatal Care (ANC) serviceis a service provided to pregnant mothers according to the service standard. Quality service is formed fromservice quality dimension. This research was carried out using analytical survey through cross sectionalapproach. The research population was all pregnant mothers in the working area of Public Health Center ofTangerang City chosen through total sampling. The data were collected using questionnaire (google form).Research finding resulted that during Covid-19 pandemics, there was 72.2% of the subjects who obtainedsuitable Antenatal Care. The research concluded that service quality of ANC during Covid-19 pandemicswas in accordance with the service guidelines established by the government.